Perancangan TPS 3R Sebagai Upaya Mewujudkan Sanitasi Total Berbasis Masyarakat Kelurahan Menur Pumpungan - Anggit Salis Media Utami; Praditya Sigit Ardisty S. (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
STBM is a comprehensive approach that not only includes sanitation infrastructure development, but also emphasizes changes in community behavior and sustainable waste management. Thus, in the implementation of STBM, the 3R Waste Disposal Site (TPS) is a key component in sustainable waste management. TPS 3R refers to waste management with the 3R principles, namely Reduce, Reuse, and Recycle. However, in this case Menur Pumpungan Village still does not have a 3R-based waste processing facility. So it is necessary to plan the optimal design of TPS 3R to be applied in the future and be able to make a significant contribution in efforts to realize Community-Based Total Sanitation. To calculate the number of TPS 3R services as the basis for design, data on the population in 2023 and the waste generation rate of 2.6 liters/person/day were used. Based on the calculations made, in an effort to support the implementation of the Community-Based Total Sanitation program. The construction of TPS 3R, which is planned to be able to serve the domestic waste processing of the entire Menur Pumpungan urban village community, is expected to reduce the amount of waste entering the landfill. The total land required for operational facilities is 511.85 m2 with a TPS 3R design consisting of a 440.85 m2 waste processing area and 96 m2 of other supporting facilities..